Diabetes diminishes a typical metabolite of litchi pericarp oligomeric procyanidins (LPOPC) in urine mediated by imbalanced gut microbiota. Issue 12 (13th May 2021) - Li, Xiaopeng; Sui, Yong; Xie, Bijun; Sun, Zhida; Li, Shuyi
Abstract : Short chain fatty acid (SCFA)-producing bacteria reduced significantly in high-fat and STZ-induced diabetic rats. And the unbalanced gut microbiota may be responsible for the drop of shikimic acid in urine, a typical metabolite of LPOPC. Abstract : Animal studies and clinical trials have shown that dietary polyphenols and polyphenol-rich foods can reduce the risk of type 2 diabetes (T2D) and its complications, but how diabetes regulates the metabolism of polyphenol has not been fully elucidated. This study investigated the effects of diabetes on litchi pericarp oligomeric procyanidin (LPOPC) dynamic metabolism and its major static metabolites in urine. First, a high-fat and streptozotocin (STZ)-induced diabetic Sprague Dawley (SD) rat model was established. In the diabetic rat model, elevated fasting blood glucose, severely impaired glucose tolerance test, and increased reactive oxygen species (ROS) levels in serum and the liver were observed. Subsequently, 200 mg per kg body weight of LPOPC was administrated to control and diabetic SD rats, and the gastrointestinal tract was collected at 0.5 h, 1 h, 3 h, and 6 h. The results showed that the retention time of LPOPC was not changed in our diabetic rat model. However, the gut microbiota were significantly altered, with elevated Proteobacteria and Verrucomicrobia abundance in diabetic rats and decreased short chain fatty acid (SCFA)-producing bacteria. Interestingly, after one dose of 300 mg per kg body weight LPOPC, the total antioxidant capacity of urine in diabetic rats significantly decreased. We then tested the static metabolites of LPOPC, demonstrating that epicatechin had not changed in urine in diabetic rats, but that shikimic acid was significantly reduced in urine in diabetic rats. The changes in shikimic acid may be due to the alteration of gut microbiota and elevated ROS levels in serum.